До питання структуроутворення високоміцного чавуну при використанні діаграм стану систем «Fe- Si», «Mg-Si» та «Fe-Si-Mg» - Кропівний, В. М.; Босий, М. В.; Кузик, О. В.; Кропівна, А. В.; Молокост, Л. А.; Kropivnyi, V.; Bosyi, M.; Kuzyk, О.; Kropivna, А.; Molokost, L. (ЦНТУ, 2023)
У статті наведено результати аналізу закономірностей структуроутворення високоміцного чавуну при використанні діаграм стану систем «Fe-Si», «Mg-Si» та «Fe-Si-Mg». Розглянуто концепцію утворення графіту у високоміцному чавуні. Наведено схему формування структури високоміцного чавуну. Встановлено, що при модифікуванні розплаву чавуну в результаті істотного перерозподілу всіх розчинених у ньому елементів відбувається очищення рафінування від домішок (сірка, фосфор та ін.), що дозволяє отримувати структуру чавуну з кулястим графітом із застосуванням модифікаторів. Приведені діаграми системи «Fe-Si», «Mg-Si» та системи «Fe-Si-Mg» для розробки складу високоміцного чавуну. Аналіз даних приведених діаграм стану, показав, що всі сполуки елементів в складі сфероїдизуючих лігатур є легкоплавкими (tпл < 1300 °С) по відношенню до температури розплаву чавуну. При кристалізації чавуну з виділенням аустеніту характерна пряма мікроліквація кремнію з коефіцієнтом розподілу менше одиниці, марганець більш рівномірно розподіляється в металі, а в рідку фазу ліквують карбідостабілізуючі елементи. The purpose of the work is to establish the patterns of structural formation of high-strength cast iron using the thermodynamic theory of phase transformations and to analyze state diagrams of the components of Fe-Si-Mg ligatures. The article presents the results of the analysis of patterns of structural formation of high-strength cast iron when using state diagrams of the "Fe-Si", "Mg-Si" and "Fe-Si-Mg" systems. The concept of graphite formation in high-strength cast iron is considered. The structure formation scheme of high-strength cast iron is presented. Disclosure of the mechanism of processes of formation of spherical and vermicular graphite opens wide opportunities for controlling the structure and properties of high-strength cast iron and contributes to the development of effective technological processes for obtaining cast products for various purposes. It has been established that during the modification of cast iron melt, as a result of a significant redistribution of all elements dissolved in it, purification of impurities (sulfur, phosphorus, etc.) takes place, which allows obtaining the structure of cast iron with nodular graphite with the use of modifiers. Diagrams of the "Fe-Si", "Mg-Si" and "Fe-Si-Mg" systems for the development of the composition of high-strength cast iron are given. After analyzing the data of the given state diagrams, it was concluded that in the composition of spheroidizing ligatures, all compounds of elements are low-melting (tpl < 1300 °С) in relation to the melting temperature of cast iron. During the crystallization of cast iron with the release of austenite, a direct microliquation of silicon with a distribution coefficient less than unity is characteristic, manganese is more evenly distributed in the metal, and carbide stabilizing elements are treated in the liquid phase. The regularities of structure formation of modified cast iron under different crystallization conditions have been established. The analysis of the study of the regularities of the process of the formation of spherical and vermicular graphite and the analysis of state diagrams of the "Fe-Si-Mg" liga-tur components were performed.
On the Question of Structural Formation of High-Compression Cast Iron Using State Diagrams System "Fe-Si", "Mg-Si" and "Fe-Si-Mg"
Keywords: високоміцний чавун; структуроутворення чавуну; кулястий графіт; вермикулярний графіт; флуктуація; high-strength cast iron; structuring of cast iron; spheroidal graphite; vermicular graphite; fluctuation